A review: harnessing the positive impact of green building materials on indoor temperature - Samsul Rijal, Nurhidayah; Zainal Abidin, Zaimah; Ramlan, Muhammad Ruzaini; Abd Rased, An Nisha Nur Welliana (Universiti Teknologi MARA, Perak, 2025)
Implementing environmentally friendly construction materials has emerged as a potential strategy to regulate indoor temperature sustainably. This is in response to the growing concerns on the comfort of interior spaces and the effects of climate change. Sustainable building methods and green building materials capacity to regulate interior temperature are becoming more widely recognized, but their effectiveness and practicality are still unclear. Many studies have explored the thermal characteristics of individual green building materials, but there is a lack of research on how these materials collectively affect indoor temperature control. This article clarifies the beneficial effects of green building materials on indoor temperature regulation by conducting a systematic literature review. This study aims to thoroughly understand how green building materials influence the dynamics of interior temperature by methodically discover, analyse, and synthesize pertinent research data. The methods for harnessing the positive impact of green building materials on indoor temperatures, such as the selection of high-quality green materials, high-performance insulating materials, high thermal mass materials and strategic placement are studied through the literature review. The results of this research do not only enhance .